2015
DOI: 10.1111/ajo.12395
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of subsequent miscarriage risk in women who present with a viable pregnancy at the first early pregnancy scan

Abstract: We have developed a new prediction model which indicates the likelihood of miscarriage. In women who present with a viable IUP at the primary scan, advancing maternal age in the presence of clots PV increases the probability of subsequent miscarriage. Whereas, in women with a higher EHR in the presence of an increased GS volume/CRL ratio, the likelihood of subsequent miscarriage is reduced. This new model outperforms the previously published model developed in our unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Women who presented with vaginal bleeding, especially those having moderate or heavy bleeding, or blood clot per vagina were likely to subsequently miscarry. 9 In this issue of the Hong Kong Medical Journal, Wan et al 7 show similar findings. Interestingly, the authors found that moderate/ severe abdominal pain is a risk factor on univariate analysis, but this finding was not confirmed on multivariate analysis probably because vaginal bleeding was a cofounding factor.…”
mentioning
confidence: 69%
“…Women who presented with vaginal bleeding, especially those having moderate or heavy bleeding, or blood clot per vagina were likely to subsequently miscarry. 9 In this issue of the Hong Kong Medical Journal, Wan et al 7 show similar findings. Interestingly, the authors found that moderate/ severe abdominal pain is a risk factor on univariate analysis, but this finding was not confirmed on multivariate analysis probably because vaginal bleeding was a cofounding factor.…”
mentioning
confidence: 69%
“…7,8 A score that signifies the likelihood of a viable pregnancy may be helpful for clinicians working in EPACs. 9,10 This score would enable clinicians to target appropriate early psychological or clinical support, thereby minimising psychological morbidity, especially for patients with finite resources. Probability models to predict pregnancy viability have been reported; these combine clinical history, sonographic assessment of gestational sac and heart pulsation, and biochemical measurements.…”
Section: Implications For Clinical Practice or Policymentioning
confidence: 99%
“…The risk of pregnancy loss is 2-5% after the recognition of heart function, 5% for women who report two miscarriages and finally 1% of women mentioning more than three miscarriages [1,11,12]. • TVS (transvaginal ultrasound) [1,[13][14][15][16][17][18][19][20].…”
Section: Recurrent Miscarriagesmentioning
confidence: 99%
“…It is of great importance in thrombophilia examinations control to include V Leiden factor and prothrombin 20210 mutation [1,[15][16][17][18][19][20].…”
Section: Laboratory Checkmentioning
confidence: 99%